PENGARUH KETAATAN BERIBADAH TERHADAP KESEHATAN MENTAL MAHASISWA UIN SUNAN AMPEL SURABAYA - Muhammad Adfan Majdi; Khodijah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of religious obedience on students of UIN Sunan Ampel Surabaya. The researcher used all students of UIN Sunan Ampel Surabaya as the population, then several samples were taken using the Stratified Sampling technique. Data were obtained through scales and questionnaires of religious obedience and mental health which were then analyzed using parametric inferential statistical techniques and tested using the t-test and simple regression analysis. The results confirmed that there was an influence of religious obedience on the health of students of UIN Sunan Ampel Surabaya. The high and low levels of their obedience in worship also influenced the high and low levels of their health. The mental health of students had an average of 78.2000 with a standard deviation of 6.14175 while religious obedience was at an average of 94.3636 with a standard deviation of 6.58985, F of 47.096 and p value (significance) of 0.000.